Beyond the asylum : mental illness in French colonial Vietnam - Edington, Claire E., 1984- (Studies of the Weatherhead East Asian Institute, Columbia University., 2019)
"This book looks beyond the asylum to consider how psychiatry in French colonial Vietnam was produced in everyday exchanges between lay people and experts"--